Monetary policy rules in the pre-EMU era: Is there a common rule? - Maria Eleftheriou; Dieter Gerdesmeier; Barbara Roffia (European Central Bank (ECB), 2006)
Despite the great importance and final success of the convergence process that led to the establishment of the European Monetary Union, there is no clear agreement regarding the monetary policy pursued in the member countries during the convergence process. This paper contributes to the literature with an empirical analysis of the period from 1993 to 1998 that encompasses eleven EMU countries. In particular, Taylor type interest rate rules are estimated with monthly national data to find that, despite certain similarities and exceptions, the rule followed by each country is distinct and differs substantially from the standard Taylor rule. However, for most countries, the parameter estimates reflect the principles proclaimed by the monetary policy authorities and, in addition, it is shown that in most cases the estimated rules reproduce the policy setting quite closely.
Keywords: E58; F41; 330; ERM; monetary policy; output gap; Taylor rule; Geldpolitik; Taylor-Regel; Produktionspotenzial; Eurozone; EU-Staaten